A component-oriented programming for embedded mobile robot software - A. Jawawi, Dayang N.; Mamat, Rosbi; Deris, Safaai (IN-TECH, 2007)
Applying software reuse to many Embedded Real-Time (ERT) systems poses significant challenges to industrial software processes due to the resource-constrained and real-time requirements of the systems. Autonomous Mobile Robot (AMR) system is a class of ERT systems, hence, inherits the challenge of applying software reuse in general ERT systems. Furthermore, software reuse in AMR systems is challenged by the diversities in terms of robot physical size and shape, environmental interaction and implementation platform Thus, it is envisioned that component-based software engineering will be the suitable way to promote software reuse in AMR systems with consideration to general requirements to be self-contained, platform-independent and real-time predictable. A framework for component-oriented programming for AMR software development using PECOS component model is proposed in this paper. The main features of this framework are: (1) use graphical representation for components definition and composition; (2) target C language for optimal code generation with resource-constrained micro-controller; and (3) minimal requirement for run-time support. Real-time implementation indicates that, the PECOS component model together with the proposed framework is suitable for resource constrained embedded AMR systems software development.